Serum Albumin Levels of Oral Candidiasis Immunosuppressed Rats Treated With Hyperbaric Oxygen - Pargaputri, Agni Febrina; Andriani, Dwi (International Journal of Integrated Health Sciences, 2020)
Objective: To investigate serum albumin levels in oral candidiasis immunosuppressed rats treated with hyperbaric oxygen. One of the predisposing factors for oral candidiasis was the use of immunosuppressive drugs continuously. It can also affect the work of the liver because it’s one of the organs responsible for drug metabolism. Hyperbaric oxygen therapy was used not only to suppressing fungal infections, but also to improve liver function by evaluating the serum albumin levels.Methods: This study used a post-test only control group design. Fifteen Wistar rats were divided into 3 groups(n=5/3): G1 (healthy group), G2 (oral candidiasis immunosuppressed rats group without hyperbaric oxygen therapy), and G3 (oral candidiasis immunosuppressed rats group with hyperbaric oxygen therapy). G2 and G3 groups were immunosuppressed by giving dexamethasone 0,5mg/day/rat orally for 14 days, added with tetracycline 1 mg/day/rat. Hyperbaric oxygen therapy was given to the G3 group in 5 days. Blood serum of rats in all groups was taken to calculate albumin levels.Results: The average value of albumin levels in G2 group showed a decrease compared to the G1 group, while G3 showed the highest level. One way Anova test showed a significant difference among groups (p<0,05). To compare the difference between each group we used LSD test and showed a significant difference (p<0,05) between G1 compared to G2, G1 compared to G3, and G2 compared to G3.Conclusion: Liver albumin levels of oral candidiasis immunosuppressed rats treated with hyperbaric oxygen therapy showed higher levels than those without therapy.